Evaluating the therapeutic effect of vitamin D and nerolidol on lung injury due to experimental myocardial infarction: The potential role of asprosin and spexin - Kocaman, Nevin (Churchill Livingstone, 2024)
Injury to internal organs caused by myocardial infarction (MI), although often neglected, is a very serious condition which damages internal organs especially the lungs. Changes in microcirculation can begin with acute lung injury and result in severe respiratory failure. The aim of this study was to create new approaches that will explain the pathophysiology and treatment of the disease by examining the therapeutic effects of vitamin D (VITD) and Nerolidol (NRD) on the injuries of the lungs caused by MI, and their relationship with asprosin / spexin proteins. Methods: Six groups of seven experimental animals each were constituted. Control, VITD (only 50 IU/day during the experiment), NRD (only 100 mg/kg/day during the experiment), MI (200 mg/kg isoproterenol was administered to rats as a single dose subcutaneously), MI+VITD (200 mg/kg isoproterenol +50 IU/day) and MI+NRD (200 mg/kg isoproterenol +100 mg/kg/day) were the six (6) groups constituted. Tissues were analyzed using histopathological and immunohistochemical methods, whereas serum samples were analyzed using ELISA method. Results: The result of the histopathological study for the MI group showed an observed increase in inflammatory cells, congestion, interalveolar septal thickening, erythrocyteloaded macrophages and fibrosis in the lung tissues. The treatment groups however recorded significant differences with regards to these parameters. In the immunohistochemical analysis, expressions of asprosin and spexin were observed in the smooth muscle structures and interalveolar areas of the vessels and bronchioles of the lung, as well as the bronchiole epithelium. There was no significant difference between the groups in terms of asprosin and spexin expression in the bronchiol epithelium. When immunohistochemical and serum ELISA results were examined, it was observed that asprosin levels increased significantly in the lung tissues of the MI group compared to the control group, decreased significantly in the treatment groups treated with Vitamin D and NRD after MI. While spexin decreased significantly in the MI group compared to the control group, it increased significantly in the MI+(VITD)-T-center dot group, but did not change in the MI+NRD group. Conclusion: It was observed that serious injuries occurred in the lungs due to myocardial infarction and that, VITD and NRD treatments had a curative effect on those injuries. It was also observed that Asprosin and Speksin proteins can have effect on mechanisms of both injury and therapy of the lung. Furthermore, the curative effects of VITD are dependent on the expression of asprosin and spexin; whereas the observation indicated that nerolidol could be effective through asprosin-dependent mechanisms and specisin by independent mechanisms.
Keywords: Myocardial Infarction; Lung damage; Nerolidol; Vitamin D; Asprosin; Spexin